2022
DOI: 10.3389/fchem.2022.985578
|View full text |Cite
|
Sign up to set email alerts
|

Insights into AIE materials: A focus on biomedical applications of fluorescence

Abstract: Aggregation-induced emission (AIE) molecules have garnered considerable interest since its first appearance in 2001. Recent studies on AIE materials in biological and medical areas have demonstrated that they show their promise as biomaterials for bioimaging and other biomedical applications. Benefiting from significant advantages of their high sensitivity, excellent photostability, and good biocompatibility, AIE-based materials provide dramatically improved analytical capacities for in vivo detection and demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…This enhancement can be attributed to the restriction of intramolecular motion (RIM) after AIEgen enrichment on the surface of Mm (in the aggregated state), resulting in bright fluorescence being observed, unlike in good solvents where fluorescence is weak. [ 40,41 ] The visible fluorescence images and concentration‐dependent PL intensity affirm that AIEgens possess a strong affinity to Mm , making them promising candidates for mycobacterial imaging.…”
Section: Resultsmentioning
confidence: 93%
“…This enhancement can be attributed to the restriction of intramolecular motion (RIM) after AIEgen enrichment on the surface of Mm (in the aggregated state), resulting in bright fluorescence being observed, unlike in good solvents where fluorescence is weak. [ 40,41 ] The visible fluorescence images and concentration‐dependent PL intensity affirm that AIEgens possess a strong affinity to Mm , making them promising candidates for mycobacterial imaging.…”
Section: Resultsmentioning
confidence: 93%
“…However, in some cases, the opposite effect has been also observed. This phenomenon, known as aggregation-induced emission (AIE), has garnered considerable interest in recent years, not only as a property of individual substances but also as a whole area of research encompassing the development of new fluorescent labels for living systems and various new materials [ 39 , 40 , 41 , 42 , 43 ]. We found that majority of the compounds described in the article are characterized by pronounced fluorescence in a solid crystalline form ( Supplementary Materials —Solid-State and Aggregation-Induced Emission, Figures S14 and S15 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, pyrene derivatives, including azole-appended ones, are known to exhibit a well-pronounced fluorescence “turn-off” response toward common nitroatomatic analytes [ 43 , 44 , 45 , 46 , 47 , 48 ], as well as some nitroaliphatic explosive components [ 49 , 50 ]. In addition, fluorescence- and aggregation-induced emission (AIE)-based small/single-molecule fluorophores, sensors, and probes [ 51 , 52 , 53 , 54 ] are of high demand for biovisualization applications [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Therefore, as a final step, we studied the ability of the present POPOP aza -analogs 3 to detect nitroanalytes.…”
Section: Resultsmentioning
confidence: 99%